The spirit moves West : Korean missionaries in America - Kim, Rebecca Y., 1974- (Oxford ; New York : Oxford University Press, 2015)
With the extraordinary growth of Christianity in the global south has come the rise of "reverse missions," in which countries in Asia, Africa, and Latin America send missionaries to re-evangelize the West. In The Spirit Moves West, Rebecca Kim uses South Korea as a case study of how non-Western missionaries target Americans, particularly white Americans. She draws on four years of interviews, participant observation, and surveys of South Korea's largest non-denominational missionary-sending agency, University Bible Fellowship, in order to provide an inside look at this growing phenomenon. Known as the "Asian Protestant Superpower," South Korea is second only to the United States in the number of missionaries it sends abroad: approximately 22,000 in over 160 countries. Conducting her research both in the US and in South Korea, Kim studies the motivations and methods of these Korean evangelicals who have, since the 1970s, sought to "bring the gospel back" to America. By offering the first empirically-grounded examination of this much-discussed phenomenon, Kim explores what non-Western missions will mean to the future of Christianity in America and around the world.--Publisher description.
Korean Protestantism and UBF -- Korean missionaries in America -- Spirit moves West, with soldier spirit -- Theology of sacrifice -- Privilege whites -- Criticisms and conflicts -- Evolution of a Korean mission movement in America -- Hyper-Korean evangelicals and American global Christianity.
Includes bibliographical references and index.
Keywords: Missions, South Korean -- United States; Evangelistic work -- United States; Evangelistic work -- Korea (South); University Bible Fellowship -- Missions -- United States; Protestantism -- Korea (South) -- History